2002
DOI: 10.1200/jco.20.6.1692
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of KIT Tyrosine Kinase Activity: A Novel Molecular Approach to the Treatment of KIT-Positive Malignancies

Abstract: Targeted therapy to inhibit the kinase activity of KIT is a rational approach to the treatment of KIT-positive malignancies. Two key factors are the potency of a given inhibitor and the relative contribution of KIT activation to the growth of the tumor. Given our current understanding of KIT activity in human malignancy, the best candidate diseases for treatment with KIT inhibitors are GIST, mastocytosis, seminoma and possibly some cases of AML. Additionally, KIT inhibitors may play an adjunctive role in disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
215
1
7

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 444 publications
(227 citation statements)
references
References 93 publications
4
215
1
7
Order By: Relevance
“…PDGFRs, as well as KIT, belong to the type III receptor tyrosine kinases, and can be specifically treated by tyrosine kinase inhibitors such as imatinib mesylate (STI571). 22 A recent study has demonstrated that imatinib mesylate inhibits ovarian cancer cell proliferation and PDGF-induced S-phase entry through PDGFR-a and Akt inactivation. 23 Although a phase II trial of imatinib mesylate as a single agent failed to produce satisfactory efficacy against recurrent and platinum-resistant ovarian cancer, 24 cases with clear-cell adenocarcinoma were not enrolled and, therefore, the effect of imatinib or other tyrosine kinase inhibitors on ovarian clear-cell adenocarcinoma remains undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…PDGFRs, as well as KIT, belong to the type III receptor tyrosine kinases, and can be specifically treated by tyrosine kinase inhibitors such as imatinib mesylate (STI571). 22 A recent study has demonstrated that imatinib mesylate inhibits ovarian cancer cell proliferation and PDGF-induced S-phase entry through PDGFR-a and Akt inactivation. 23 Although a phase II trial of imatinib mesylate as a single agent failed to produce satisfactory efficacy against recurrent and platinum-resistant ovarian cancer, 24 cases with clear-cell adenocarcinoma were not enrolled and, therefore, the effect of imatinib or other tyrosine kinase inhibitors on ovarian clear-cell adenocarcinoma remains undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…However, the higher rate of c-kit expression in malignant phyllodes tumors in our study was comparable to these series. 9,10 In view of the action of the newly developed phenylaminopyrimidine derivative STI571 (Glivec, Novartis), which inhibits tyrosine kinase receptors, and its usefulness in gastrointestinal stromal tumors, 21 the drug may theoretically also be useful in the management of malignant phyllodes tumor, particularly with tumor recurrences or distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…In some cancers such as gastro intestinal stromal tumours (GISTs), point mutations lead to abnormal expression and constitutive activity of the receptor. CD117 is targeted there by imatimib mesylate (Heinrich et al, 2002).…”
mentioning
confidence: 99%